2022
DOI: 10.1016/j.jgr.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng inhibits methamphetamine addictive behaviors by regulating dopaminergic and NMDAergic system in rodents

Abstract: Background Methamphetamine (METH) is the most widely used psychostimulant and has been known to exhibit reinforcing effects even after long abstinence. We showed the inhibitory effect of Korean Red Ginseng extract (RGE) on METH-induced addictive behaviors in animal models mimicking the human drug-use pattern. Methods We first investigated the effect of RGE on the acquisition of METH-induced dependence using self-administration and conditioned place preference (CPP) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Moreover, METH increased the expression of proteins related to dopamine function, including DAT, which is responsible for dopamine clearance, TH, the dopamine synthetase, and the D 1 (D 1 receptor) and the D 2 -dopamine receptors (D 2 receptor), which mediate dopamine signalling, only in WT but not in TRPA1 KO mice. Overexpression of these proteins may be a compensatory mechanism for METH-induced overactivation of the dopamine system, as shown in previous rodent studies (Chauhan et al, 2014;Fibiger & McGeer, 1971;Lee et al, 2021;Thompson et al, 2015) and in patients with METH use disorder (Worsley et al, 2000). The present studies also showed that METH increased PKA and PKC expression only in WT mice.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, METH increased the expression of proteins related to dopamine function, including DAT, which is responsible for dopamine clearance, TH, the dopamine synthetase, and the D 1 (D 1 receptor) and the D 2 -dopamine receptors (D 2 receptor), which mediate dopamine signalling, only in WT but not in TRPA1 KO mice. Overexpression of these proteins may be a compensatory mechanism for METH-induced overactivation of the dopamine system, as shown in previous rodent studies (Chauhan et al, 2014;Fibiger & McGeer, 1971;Lee et al, 2021;Thompson et al, 2015) and in patients with METH use disorder (Worsley et al, 2000). The present studies also showed that METH increased PKA and PKC expression only in WT mice.…”
Section: Discussionsupporting
confidence: 87%